Обзор веснянок (Plecoptera) Украинских Карпат. II. Семейства Leuctridae, Capniidae, Perlodidae, Perlidae, Chloroperlidae - Жильцова, Л.А. (Вестник зоологии, 1968)
In the Ukrainian Carpathians fauna Plecoptera of the family Leuctridae is presen-ted by 17 species, Capniidae — 4, Perlodidae — 9, Perlidae— 6, Chloroperlidae —5. Three of them are mentioned for the first time for the USSR fauna. A greater part of the species is found in the forest belt and in elfin woodland. In high mountain pastures Plecoptera is very rare. The zoogeographical analysis of the whole fauna is given in the first communication (aoological Record, 1967, No. 4).